Gender Representation in @amer_al_jazie Caricatures: A Critical Discourse Analysis of Women's Social Roles - Susilawati; Abdul Muntaqim Al Anshory (Center of Language and Cultural Studies, 2025)
The focus of this research is to analyze the representation of women's social roles in Amer Al-Jazie's caricatures on the Instagram account @amer_al_jazie using Sarah Mills' Critical Discourse Analysis (CDA) approach. Using a qualitative descriptive method, this study highlights four caricatures that display gender construction in Iraqi society. The results show that Amer Al-Jazie's caricatures represent the social role of women with a critical approach to the social construction of gender in Iraq. On the one hand, it criticizes patriarchy and traditional gender norms that oppress women, but on the other hand, it maintains certain gender stereotypes, which place men as the dominant party. Women are represented in various positions, both as subjects with agency and as objects controlled by patriarchal social structures. In Aljazie's caricatures, women are often positioned as individuals who are under social pressure, controlled and judged, whether in social media, state policies, households, or community norms, while men have more agency in determining their own roles and the roles of women.